EMBRYO DEVELOPMENT AND ENDOGENOUS NUTRIENT ABSORBTION OF SEA SILVER POMPANO FISH LARVAE FROM NATURAL SPAWN OF BROODSTSOCK, Trachinotus blocii, (LACEPEDE) - Tony Setia Dharma (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Silver pompano is a prospective high value commodity to be developed in mariculture. The aims of this research were to understand the development of embryo and absorption pattern of endogenous nutrient at the time of changing from using endogenous to exogenous nutrient. This research was conducted in Institute for Mariculture Research and Development, Gondol, Singaraja, Bali using fertilized eggs which were stocked in concrete tanks 3 m3, filled with 2 m3 of seawater, in a density of 25 eggs/l. Temperature at the time of hatching was 28-30oC. The observation of embryo development and its morphology was performed after hatching by collecting larvae as many as 10. Parameters measured were total length of larvae (TL), yolk sac volume (VK), oil globule volume (VM) and larvae development. The results showed that embryo of silver pompano had a normal development, consisted of several phases i.e., fertilized egg, cell division, neurola, gastrula, complete embryo and hatching as larvae. Newly hatched larvae had endogenous nutrient as yolk sac and oil globule with volume of 2.27.10-1 mm3 ± 0.06 and 5.57.10-1 mm3 ± 0.02, respectively. Yolk sac was completely absorbed after 35:30 to 46:30 hours and oil globule after 52:30 to 64:30 hours. Initial feeding was given when yolk sac was completely absorbed but before oil globule was completely absorbed. The average total length of larvae was 2.40 ± 0.10 mm. Keywords: embryo, larvae, absorption, yolk sac, silver pampano